اليات مواجهة جريمة التمييز و خطاب الكر اهية في الالتشريع الجزائري من خلال القانون 05/20 - (:unkn) unknown (جامعة المسيلة, 2025)
The increasing dangers posed by discrimination and hate speech within Algerian society prompted the Algerian legislator to enact Law 20/05 to combat this crime and reduce its risks. This law outlines the key elements that constitute this offense and establishes a set of mechanisms to address it, including both punitive and preventive measures. Regarding punitive mechanisms, the law stipulates a range of primary penalties that vary according to the severity of the crime, as well as supplementary penalties. As for the preventive mechanisms, they include the establishment of the National Observatory for Combating Discrimination and Hate Speech, in addition to involving civil society actors, the educational system, and the media in awareness and sensitization efforts to counter discrimination and hate speech.